2022
DOI: 10.1098/rsta.2021.0385
|View full text |Cite
|
Sign up to set email alerts
|

Frontal waves and transmissions for temporal laminates and imperfect chiral interfaces

Abstract: The analysis of wave patterns in a structure which possesses periodicity in the spatial and temporal dimensions is presented. The topic of imperfect chiral interfaces is also considered. Although causality is fundamental for physical processes, natural wave phenomena can be observed when a wave is split at a temporal interface. A wave split at a spatial interface is a more common occurrence; however, when the coefficients of the governing equations are time-dependent, the temporal interface becomes important. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This jump is governed by the velocity g at time t=0. It is also observed that, when the gravity is finite, the jump conditions across the temporal chiral interface are not affected by gravity, and are similar to those studied in [20].…”
Section: Transition Regime For the Case Of A Large Gyricitysupporting
confidence: 71%
See 3 more Smart Citations
“…This jump is governed by the velocity g at time t=0. It is also observed that, when the gravity is finite, the jump conditions across the temporal chiral interface are not affected by gravity, and are similar to those studied in [20].…”
Section: Transition Regime For the Case Of A Large Gyricitysupporting
confidence: 71%
“…The applications of the dynamic materials with temporal interfaces are discussed in [15,19], and the wave patterns in such materials are also analysed in [16][17][18]20].…”
Section: (B) a Temporal Chiral Interface Of High Gyricitymentioning
confidence: 99%
See 2 more Smart Citations
“…We could further explore optimal design of time-modulated media [51]. As another perspective, our asymptotic analysis can be applied to time-modulated conductivity, hydrodynamic and elasticity equations (we note in passing the fascinating work [52] on temporal elastic laminates with imperfect chiral interfaces), as well as other governing equations in physics described by linear partial differential equations, where we expect that similar non-reciprocal effects can be unveiled in the homogenization regime. Another perspective concerns the case of locally resonant media [53,54], to combine both low-frequency non-reciprocity and low-frequency resonances for more important macroscopic effects.…”
Section: Discussionmentioning
confidence: 99%